2012
DOI: 10.1021/ac302245t
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Photoswitching of Spiropyran-Conjugated Semiconducting Polymer Dots

Abstract: Semiconducting polymer dots (Pdots) recently have emerged as a new class of ultrabright fluorescent probes with promising applications in biological detection and imaging. We developed photoswitchable Pdots by conjugating photochromic spiropyran molecules onto poly[9,9-dioctylfluorenyl-2,7-diyl)-co-1,4-benzo-{2,1′-3}-thiadiazole)] (PFBT). The modulation of fluorescence was achieved by ultraviolet irradiation, which converted spiropyran into its visible-absorbing merocyanine form. The merocyanine efficiently qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
85
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 54 publications
0
85
0
Order By: Relevance
“…These polymer dots, referred to as CPdots and later Pdots, are made from semiconducting polymer materials such as PPE, PFPV, or PFBT (see Figure 6.8 for full chemical name), are $4 nm in diameter with high fluorescent intensities, and could be readily functionalized [140][141][142]. Others have studied these Pdot materials, including Chan et al who developed FRET-based Pdots with photoswitching capabilities [143,144]. These were created through the incorporation of photochromic spiropyran molecules into a PFBT polymer and were intended for use in bioimaging applications.…”
Section: Dendrimers and Polymer Macromoleculesmentioning
confidence: 99%
“…These polymer dots, referred to as CPdots and later Pdots, are made from semiconducting polymer materials such as PPE, PFPV, or PFBT (see Figure 6.8 for full chemical name), are $4 nm in diameter with high fluorescent intensities, and could be readily functionalized [140][141][142]. Others have studied these Pdot materials, including Chan et al who developed FRET-based Pdots with photoswitching capabilities [143,144]. These were created through the incorporation of photochromic spiropyran molecules into a PFBT polymer and were intended for use in bioimaging applications.…”
Section: Dendrimers and Polymer Macromoleculesmentioning
confidence: 99%
“…[42][43][44][45] On the other hand, it was also reported that the ACPs incorporated with photochromic moieties showed reversible photomodulation of the fl uorescence by using light stimuli. [46][47][48] In these polymer systems, the fl uorescent moiety is independent of the photochromic moiety, resulting in high fl exibility on the molecular design.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] One of the most important classes of chromogenic materials is photochromic 6-nitro-1′,3′-dihydrospiro[chromene-2,2′-indoles], also known in the literature as 6-nitrospiro[2H-1-benzopyran-2,2′-indolines], which have been extensively studied due to their potential applications in various areas of materials science and advanced technologies. [5][6][7][8] The aforementioned compounds under UV-irradiation undergo rapid C-O bond cleavage, converting to the planar, coloured trans-merocyanine form. 9,10 The synthesis of 1′,3′-dihydrospiro-[chromene-2,2′-indoles] is usually based on the condensation of 2-methylideneindoline derivatives with such aryl aldehydes as 5-nitrosalicylaldehyde.…”
Section: Introductionmentioning
confidence: 99%